PERTANGGUNGJAWABAN PIDANA DALAM TINDAK PIDANA KEKERASAN SEKSUAL TINJAUAN YURIDIS ATAS IMPLEMENTASI UU TPKS DAN KUHP NASIONAL - Rahmat Wijaya; Siti Humulhaer; Agus Alqodri; Gunarto Wardono; Raliyanto Budi Wikarno (CV. Lafadz Jaya, 2026)
Sexual violence constitutes a fundamental crime against humanity that requires a comprehensive legal response grounded in a victim-centered perspective. This paper analyzes the construction of criminal liability in cases of sexual violence following the enactment of Law Number 12 of 2022 on Sexual Violence Crimes and the Indonesian National Criminal Code (KUHP). This research employs a normative juridical method using statutory, conceptual, and case approaches. The analysis shows that the Sexual Violence Law functions as lex specialis regulating sexual violence offenses comprehensively, while the National Criminal Code provides a general legal framework with a progressive expansion of the definition of rape under Article 473. The concept of criminal liability has evolved from a paradigm centered on physical violence toward one emphasizing violations of bodily autonomy and consent. However, its implementation faces challenges, including cross-sectoral coordination, limited institutional capacity of law enforcement officials, and persistent social stigma. This paper recommends strengthening victim assistance systems, enhancing forensic capacity, and harmonizing legal regulations in order to achieve restorative justice.